Causes of death and clinical characteristics of 34 patients with Mucopolysaccharidosis II in Taiwan from 1995–2012. Issue 1 (December 2016) - Lin, Hsiang-Yu; Chuang, Chih-Kuang; Huang, Yu-Hsiu; Tu, Ru-Yi; Lin, Fang-Ju; Lin, Shio; Chiu, Pao; Niu, Dau-Ming; Tsai, Fuu-Jen; Hwu, Wuh-Liang; Chien, Yin-Hsiu; Lin, Ju-Li; et al.
Abstract Background Mucopolysaccharidosis type II (MPS II) is an X-linked recessive, multisystemic lysosomal storage disorder caused by a deficiency of iduronate-2-sulfatase. MPS II has a variable age of onset and variable rate of progression. In Asian countries, there is a relatively higher incidence of MPS II compared to other types of MPS. Methods A retrospective analysis was carried out of 34 Taiwanese MPS II patients who died between 1995 and 2012. The clinical characteristics, medical records, age at death, and cause of death were evaluated to better understand the natural progression of this disease. Results The mean age at death of 31 of the patients with a severe form of the disease with significant cognitive impairment was 13.2 ± 3.2 years, compared with 22.6 ± 4.3 years in the three patients with a mild form of the disease without cognitive involvement (n = 2) or the intermediate form (n = 1) (p < 0.001). The mean ages at onset of symptoms and confirmed diagnosis were 2.5 ± 2.1 and 4.8 ± 3.1 years, respectively (n = 32). Respiratory failure was the leading cause of death (56 %), followed by cardiac failure (18 %), post-traumatic organ failure (3 %), and infection (sepsis) (3 %) (n = 27). Age at onset of symptoms was positively correlated with life expectancy (p < 0.01). Longevity gradually increased over time from 1995 to 2012 (p < 0.05). Conclusions Respiratory failure and cardiac failure were the two major causes of death in these patients. The life expectancy of Taiwanese MPS II patients has improved in recent decade.